English Diphthongs Pronunciation Errors Found in North Bali Bilingual School’s 5th Grade Students - Putri Karisma Sari; Ni Luh Ketut Mas Indrawati; I Nyoman Aryawibawa (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This undergraduate thesis examines English diphthong pronunciation errors among fifth-grade students at North Bali Bilingual School, with a specific focus on centring and opening diphthongs using Peter Roach's theory. The primary aim is to identify the errors made by the students and determine the underlying factors contributing to these errors. The research employs a qualitative method supported by quantitative data, involving voice recordings collected via VoiceMemos on an iPhone, which were then phonetically transcribed. Additionally, a questionnaire was administered to gather background information on the students that might explain the pronunciation errors. The findings reveal that while the majority of students can correctly produce diphthong sounds, 22% of them made pronunciation errors. The most frequently mispronounced diphthongs were /ɪə/ with 75% errors, /ɑʊ/ with 59% errors, and /eə/ with 25% errors. The questionnaire results suggest that the primary factors contributing to these errors include the students' native language, phonological interference, avoidance strategies, and potential neurodevelopmental disorders. The research provides insights into the specific challenges faced by bilingual students in mastering English diphthongs and highlights the need for targeted interventions to address these pronunciation issues.